The Fund's Income Position for FY 2006 : Update to the Midyear Review. (Policy Papers; Policy Paper ;, 2006)
This paper provides updated information on the Fund's income position. The regular midyear review of the Fund's income for FY 2006 was completed by the Executive Board on December 9, 2005. That review projected a small shortfall of SDR 18 million from the regular net income target of SDR 188 million. The projection was based on the usual set of assumptions, including that repurchases would be made as scheduled.